Polyimide-silica hybrid coatings: morphological, mechanical, and thermal investigations - (:unkn) unknown (WILEY, 2007)
In this study, polyimide-silica (PI-silica) based hybrid coating compositions were prepared from tetraethoxysilane (TEOS), gamma-glycidyloxypropyl trimethoxy silane (GOTMS), and polyamic acid (PAA) via a combination of sol-gel and thermal imidization techniques. PAA was synthesized from 3,3 ',4,4 '-benzophenone tetracarboxylic dianhydride (BTDA) and 3,3 '-Diaminodiphenyl sulfone (DDS) in N-Methyl-2-pyrrolidone (NMP). The silica content in the hybrid coatings was varied from 0 to 20 wt%. The structural characterization of the hybrid coatings was performed using FTIR and Si-29-NMR spectroscopies. Results from both pendulum hardness and micro indentation test show that the hardness of hybrid coatings improves with the increase in silica content. The tensile tests also demonstrated that the mechanical properties at low silica content are rather striking. Their surface morphologies were characterized by scanning electron microscopy (SEM). SEM studies revealed that inorganic particles were distributed homogenously through the PI matrix. It was also found that, incorporation of the silica domains increased the thermal stability of the hybrid coatings. Copyright (C) 2007 John Wiley & Sons, Ltd.
Keywords: polyimide; organic-inorganic hybrid; sol-gel technique; polyimide-silica hybrid; SOL-GEL PROCESS; COUPLING AGENTS; NANOCOMPOSITES; FILMS; COMPOSITES; MEMBRANES; BEHAVIOR